Pengaruh Sales Growth, Transfer Pricing dan Beban Pajak Tangguhan terhadap Tax Avoidance - Firda Musliha Pasha; Adhitya Putri Pratiwi (P3M Politeknik Negeri Bengkalis, 2025)
This study aims to analyze the effect of Sales Growth, Transfer Pricing and deferred tax expense on Tax Avoidance. This type of research is quantitative research with secondary data sources. The research population includes 130 companies in the consumer non cyclicals sector that listed on the Indonesia Stock Exchange in 2019-2023. The sample selection method used in this study was purposive sampling so that the final sample obtained by this method was 8 companies for the period 2019-2023 with a total research sample of 40 sample data. The analysis method uses panel data regression analysis techniques with the help of the E-Views 12 program. The results showed that the best model was the Common Effect Model (CEM). The results showed that Sales Growth, Transfer Pricing and Deferred Tax Expenses simultaneously affect on Tax Avoidance. The results obtained show that partially that Sales Growth (X1) and Deferred Tax Expenses (X3) have an influence on Tax Avoidance (Y) while for the Transfer Pricing variable (X2) has no effect on the Tax Avoidance variable (Y).